THE INFLUENCE OF LEARNING DISCIPLINE AND LEARNING MOTIVATION ON STUDENTS’ LEARNING OUTCOMES IN THE OFFICE MANAGEMENT AND BUSINESS SERVICES PROGRAM AT SMKS KRISTEN 2 TOMOHON - Sefanya Sisilia Hansun; Amsje Winokan; Listriyanti Palangda; Danny Polii (J-Shelves of Indragiri (JSI), 2025)
Academic achievement is widely recognized as one of the most crucial indicators of educational success, reflecting the extent to which students are able to attain learning objectives. It is strongly influenced by both internal and external factors that shape students’ attitudes, behaviors, and performance in the learning process. Among these factors, learning discipline and learning motivation play a particularly important role in determining students’ achievement outcomes. This study aims to examine the influence of learning discipline and learning motivation on the academic achievement of vocational high school students. The research employed a quantitative approach with a survey method. The population of the study consisted of tenth-grade students in the Office Management and Business Services program at SMKS Kristen 2 Tomohon. A total of 30 students were selected as research participants. Data were collected using structured questionnaires that measured students’ learning discipline and learning motivation, while their academic achievement was assessed through official school records. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 27 to determine the simultaneous and partial effects of the independent variables on the dependent variable. The findings reveal that both learning discipline and learning motivation have a significant and positive effect on academic achievement. The coefficient of determination (R Square) was found to be 0.949, indicating that 94.9% of the variation in academic achievement can be explained by learning discipline and learning motivation. The remaining 5.1% is attributed to other factors not included in this study, such as family background, peer influence, teaching quality, and learning environment. These results emphasize the importance of fostering consistent learning discipline and strengthening intrinsic as well as extrinsic motivation in order to improve students’ academic performance. In conclusion, the study highlights that educational institutions, teachers, and parents must work collaboratively to encourage disciplined learning habits and sustain students’ motivation, as both are proven to be strategic factors in enhancing academic achievement at the vocational school level.